2016
DOI: 10.1523/jneurosci.2141-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic Activation of Septal Glutamatergic Neurons Drive Hippocampal Theta Rhythms

Abstract: The medial septum and diagonal band of Broca (MS-DBB) has an essential role for theta rhythm generation in the hippocampus and is critical for learning and memory. The MS-DBB contains cholinergic, GABAergic, and recently described glutamatergic neurons, but their specific contribution to theta generation is poorly understood. Here, we examined the role of MS-DBB glutamatergic neurons in theta rhythm using optogenetic activation and electrophysiological recordings performed in in vitro preparations and in freel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(134 citation statements)
references
References 20 publications
8
126
0
Order By: Relevance
“…This finding is of high relevance since a recent study by Atoji et al [2016] found that glutamatergic neurons of DM project to SL, a characteristic which is shared by glutamatergic neurons in the mammalian Ammon's horn. In mammals, the septum projects back to the hippocampus and drives hippocampal theta rhythms, which are essential for learning and memory functions [Winson, 1978;Leutgeb and Mizumori, 1999;Vandecasteele et al, 2014;Robinson et al, 2016]. The lack of functional connectivity between SL and the analyzed hippocampal regions could indicate an important functional difference of SL in the avian hippocampal network.…”
Section: Septum Lateralementioning
confidence: 99%
See 1 more Smart Citation
“…This finding is of high relevance since a recent study by Atoji et al [2016] found that glutamatergic neurons of DM project to SL, a characteristic which is shared by glutamatergic neurons in the mammalian Ammon's horn. In mammals, the septum projects back to the hippocampus and drives hippocampal theta rhythms, which are essential for learning and memory functions [Winson, 1978;Leutgeb and Mizumori, 1999;Vandecasteele et al, 2014;Robinson et al, 2016]. The lack of functional connectivity between SL and the analyzed hippocampal regions could indicate an important functional difference of SL in the avian hippocampal network.…”
Section: Septum Lateralementioning
confidence: 99%
“…Interestingly, the lateral septum (SL) receives input from DM but neither SL nor medial septum have strong back projections [Atoji and Wild, 2004;Atoji et al, 2016]. The lack of strong reciprocal connectivity is an important difference to the mammalian hippocampus where the medial septum has a strong cholinergic and glutamatergic back projections to the hippocampus that drive hippocampal theta rhythms, thereby facilitating learning and memory [Winson, 1978;Leutgeb and Mizumori, 1999;Strange et al, 2014;Vandecasteele et al, 2014;Herold et al, 2015;Robinson et al, 2016]. A further critical area is the TPO (area temporo-parietooccipitalis) that has reciprocal connections with the CDL and is also connected to CDL via the dorsal thalamus [Atoji and Wild, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of medial septum inactivation could be due to loss of GABAergic input that can drive network theta rhythm activity [38], or to loss of the cellular effects of cholinergic modulation that normally shift network dynamics from sharp-wave spiking to theta rhythm dynamics [38,39] and normally enhance the influence of external sensory input [40]. The loss of spatial coding could also be due to the loss of glutamatergic input from the medial septum that contributes to coding of running speed in the hippocampus [41,42]. …”
Section: Modeling Of Spatial Memory (Grid Cells Place Cells and Splimentioning
confidence: 99%
“…Thereby activation of cholinergic MSDB neurons supports the temporal organization of neuronal spiking and synaptic inputs. Recently, (Robinson et al, 2016) showed that the optogenetic activation of glutamatergic MSDB neurons increases the rhythmicity of spontaneously generated hippocampal theta oscillations through a mechanism dependent on local septal connections. Since glutamatergic neurons can excite both cholinergic and GABAergic MSDB neurons (Xu et al, 2015), these data corroborate the hypothesis of a medial septal relay with a central role for GABAergic MSDB neurons for rhythmic control over cortex and hippocampus.…”
Section: Cholinergic Modulation Of Cortical Network Oscillatory Dymentioning
confidence: 99%